Exploring the linkage between business model (&) innovation and the strategy of the firm. (20th April 2016) - Spieth, Patrick; Schneckenberg, Dirk; Matzler, Kurt
Abstract : Research on the phenomenon of business model (&) innovation is taking place in related perspectives. Next to innovation and entrepreneurship literature, theories of firm strategy closely relate to the ongoing conceptualization of the business model concept. We first review in this article the linkage between the business model, innovating the business model and firm strategy in extant literature. We focus specifically on the explanatory power of the business model concept to develop insights for strategic firm behaviour, and we explore the role of business model innovation as analytic perspective for identifying sources of firm performance. Building on this conceptual overview, we subsequently present how the articles in this special issue contribute in the light of strategy theory to the understanding of the phenomenon of business model innovation. Finally, we develop some themes for future research on the topic.